Phase-separating peptides recruiting aggregation-induced emission fluorogen for rapid E. coli detection - Maricar, Syed (2023)
Rationally designed biomolecular condensates have found applications primarily as drug-delivery systems, thanks to their ability to self-assemble under physico-chemical triggers (such as temperature, pH, or ionic strength) and to concomitantly trap client molecules with exceptionally high efficiency (>99%). However, their potential in (bio)sensing applications remains unexplored. Here, we describe a simple and rapid assay to detect E. coli by combining phase-separating peptide condensates containing a protease recognition site, within which an aggregation-induced emission (AIE)-fluorogen is recruited. The recruited AIE-fluorogen’s fluorescence is easily detected with the naked eye when the samples are viewed under UV-A light. In the presence of E. coli, the bacteria’s outer membrane protease (OmpT) cleaves the phase-separating peptides at the encoded protease recognition site, resulting in two shorter peptide fragments incapable of liquid-liquid phase separation. As a result, no condensates are formed and the fluorogen remains non-fluorescent. The assay feasibility was first tested with recombinant OmpT reconstituted in detergent micelles and subsequently confirmed with E. coli K-12. In its current format, the assay can detect E. coli K-12 (10^8 CFU) within 2 h in spiked water samples and 1-10 CFU/mL with the addition of a 6-7 h pre-culture step. In comparison, most commercially available E. coli detection kits can take anywhere from 8 to 24 h to report their results. Optimizing the peptides for OmpT’s catalytic activity can significantly improve the detection limit and assay time. Besides detecting E. coli, the assay can be adapted to detect other Gram-negative bacteria as well as proteases having diagnostic relevance.